THU0456 Rate of hospitalization for heart failure is lower in patients with controlled gout versus uncontrolled gout. (15th June 2017) - Morlock, R; Chevalier, P; Klein, AB
Abstract : Background: Hyperuricemia is associated with worsened outcomes in patients with heart failure (HF). However, little is known about the association between gout and HF. Objectives: To assess the impact of gout control on the rate of hospitalization for acute HF in a prevalent gout population. Methods: This retrospective database analysis used data from the Clinical Practice Research Datalink-Hospital Episode Statistics (UK) from Jan 1, 2009 to Dec 31, 2011. Patients were required to have evidence of "prevalent established gout" (ie, treated with urate-lowering therapy [ULT] or eligible for ULT based on ACR guidelines) between Jan 1, 2009 and Dec 31, 2009 and be aged ≥18 on index date (Jan 1, 2010). Follow-up extended from Jan 1, 2010 to Dec 31, 2011. HF rate was calculated as the percentage of eligible patients having ≥1 HF-related hospitalization over the course of the calendar year. In each calendar year, patients were considered to have controlled gout if they had no elevated serum uric acid (sUA; ≥6 mg/dL), no diagnosis of tophus, and no flare documented. Uncontrolled gout was defined as ≥1 elevated sUA or 1 tophus diagnosis during the year. In this analysis patients with no documented sUA were considered not evaluable. To mitigate the limited availability of sUA data, a sensitivity analysis was conducted using an alternate definition of control status: if sUA was available, controlled was defined as no elevated sUA, no flare, and no tophi and uncontrolled was defined as ≥1 elevated sUA, tophus, or flare; if sUA was unavailable, controlled was defined as medication possession ratio (MPR)>80% and uncontrolled defined as 0%<MPR≤80%. Here, patients with no documented sUA and MPR=0% were not evaluable. The odds ratio of HF was modeled in each post-index year using logistic regression models, with adjustment for control status (in previous or current year), gender, age, and Charlson Comorbidity index as covariates. Results: A total of 29, 758 eligible gout patients were identified. Within the subset of patients with available sUA (4762 in 2010 and 4385 in 2011), the HF rate was consistently lower in patients whose gout was controlled in the ongoing year (adjusted OR: 0.253 in 2010 [ P =0.032]; 0.268 in 2011 [ P =0.019]). The sensitivity analysis conducted using MPR as a proxy for control in a larger population (26, 999 patients in 2010 and 26, 176 patients in 2011) yielded similar results (OR: 0.387 in 2010 [ P <0.001]; 0.462 in 2011 [ P <0.001]). Conclusions: This study suggests that patients with controlled gout have a lower risk of being hospitalized for HF. Further studies would be required to validate this finding on larger samples. Acknowledgements: This study was sponsored by Ardea Biosciences/AstraZeneca. Disclosure of Interest: R. Morlock Consultant for: AstraZeneca, Ironwood, Ardea Biosciences, P. Chevalier Employee of: QuintilesIMS, A. Klein Employee of: AstraZeneca